PERENCANAAN BISNIS INDUSTRI TEPUNG GLUKOMANAN PORANG (Amorphophallus oncophyllus) - Kevin Tanjung (Agroindustrial Technology Journal, 2022)
Cultivation and production of porang tubers is growing but most of the results are exports while with abundant production it can be used alone to make glucomannan flour. The production of glucomannan flour in Indonesia is currently still in the development stage and most of it is still on a laboratory scale, to develop porang agriculture and glucomannan flour is to increase the scale of production to be larger. This study aims to analyze whether the glucomannan flour industry is technically, financially and marketing feasible if it is established in Indonesia. The results showed that from a technical and technological perspective the production process of porang tubers to become glucomannan flour was feasible because at a laboratory scale there were already standards for equipment, material use and production. Financial analysis is said to be feasible based on the results of the calculation of investment feasibility which includes IRR, NPV, PI and PP because each calculation meets the criteria for eligibility. Market and marketing analysis is said to be feasible if a product has an opportunity for its market. The market and marketing analysis using the STP method shows that glucomannan flour can use segmenting to be developed into targeting which then gets the image of the product by positioning